Prokrastinasi Akademik Ditinjau dari Jurusan IPA, IPS dan Bahasa kelas XI di SMA - Sandra Arista Manune; Dian Lestari Anakaka; R. Pasifikus Christa Wijaya (Universitas Nusa Cendana, 2020)
The purpose of this study was to determine differences in academic procrastination between the majors of Natural Sciences, Social Sciences and Languages. This research uses a comparative research approach. The subjects of this study were 36 students in Class XI majoring in Natural Sciences, 34 in Social Sciences, and 33 people in Language. Data collection techniques were carried out with quantitative scale instruments that had been tested for validity and reliability. The results of this study are empirical, statistically analyzed by one way ANOVA test through the application of statistical data management. The results showed that the p value (sig) 0.001< 0.05 was strengthened by the results of the post hoc test with the highest average academic procrastination in the Language department at 102.3939 with a significance value of 0.973> 0.05. There are differences in academic procrastination between students majoring in Natural Sciences, Social Sciences and Language Classes XI IN SMA Negeri 1 Kupang Timur. Students majoring in Language are higher in procrastination academic than students majoring in Natural Sciences and Social Sciences. The lowest procrastination is students majoring in Natural Sciences and Social Sciences who are in the medium category so that teachers must pay more attention to their students by creating an effective atmosphere in learning, so that students can be motivated to learn and do the assignments without delay.